Application and Research of Gangue Partial-Filling Mining Method in Preventing Water Inrush from Floor. (21st March 2022) - Pang, Zhenzhong; Zhang, Xinguo; Chen, Juntao; Li, Feifan
Abstract : Coal gangue produced during coal production not only poses a serious threat to the ground environment but also imposes serious economic burdens on the mine. The partial-filling mining (PFM) method proposed in this paper can make full use of coal gangue and is of great significance to the prevention and control of water disasters at the working face. The specific process used to implement this method is to first divide the working face into several narrow working faces and then fill the filling body into part of the goaf. The ability of PFM to restrain floor water inrush is analyzed by physical simulation, and the field application research is carried out at the No. 9211 mining face of Bucun Coal Mine in Shandong, China. The physical simulation results show that the failure depth of this layer is less than 5 m. The field measurements reveal that the maximum compression deformation of the filling body is 89.1 mm, and the maximum floor failure depth of the floor is only 8.6 m. Comparative analysis indicates that the floor failure depth of the No. 9211 working face with the local filling method is 4.6 m lower than that of the No. 9110 working face with the strip mining method. In addition, no water inrush accident occurs at the No. 9211 working face during mining. Therefore, PFM not only controls the floor damage depth effectively but also consumes coal gangue to protect the mine environment.